PEMANFAATAN DAUN TANAMAN SUKUN (Artocarpus altilis) SEBAGAI ANTI NYAMUK MAT ELEKTRIK DALAM MEMBUNUH NYAMUK Aedes, spp - Memory Fitri Sitorus; wirsal hasan; irnawati marsaulina (Lingkungan dan Kesehatan Kerja, 2014)
Aedes,spp mosquitoes are vectors of various diseases (dengue fever, filariasis, chikungunya and yellow fever). To controll the vector borne disease can be done by controlling its vector. One of the way to control the disease is using the synthetic insecticide that are toxic to human, so it is necessary to use natural insecticide.The purpose of this study is to utilize the leaves of breadfruit plant (Artocarpus altilis) as an electrical mat to kill mosquito Aedes.This research was quasi-experimental with completely randomized design (CRD) with 6 treatments (the weight of breadfruit leaf powder of 0 mg, 100 mg, 200 mg, 300 mg, 400 mg and 500 mg) with 3 times repetitions.The result indicate that there were the difference of mosquito mortality based on the weight of each mat with three repetitions during 30 minutes observation. The mosquito mortality rate at weight of 100 mg was 33,33%, 200 mg was 40%, 300 mg was 53,33% (reached the LD 50), 400 mg was 46,67%, 500 mg was 46,67%, and there was no mortality in control. Based on the result of statistical test of one-way Anova with significance level of 5%, it was obtained that p(0,976)> α(0,05), which means there was no difference in the average number of Aedes,spp mosquitoes dead significantly.The conclusion is breadfruit leaves (Artocarpus altilis) can be used as an electrical mat to Aedes,spp, and the effective weight of breadfruit leaves to kill Aedes,spp was 300 mg.